Victimization of the Land and the Body: An Ecocritical Reading of Kamala Markanday’s Nectar in a Sieve - Koban, Haydar Jabr; Abdulsahib, Islam F.; Zapata, Jesus Varela (Journal of Posthumanism, 2025)
This study examines the intersection of environmental degradation and colonial histories through an ecocritical reading of Kamala Markanday’s postcolonial ecocritical novel, Nectar in a Sieve. (1954). Drawing from feminist ecocriticism and postcolonial theory, the analysis reveals how ecological harm is deeply intertwined with issues of race, gender, and power. It explores the victimization of both land and body as literary tropes that reflect broader sociopolitical realities, particularly in formerly colonized regions. The article engages with recent scholarship in ecocriticism and postcolonial environmental studies to highlight the ways literature articulates resistance, agency, and alternative ecological imaginaries. Ultimately, the study situates literary representations within the broader discourse of environmental justice and decolonial movements, emphasizing the potential of postcolonial narratives to challenge dominant paradigms and envision sustainable futures.